The Outcome of Cholangitis After Percutaneous Biliary Drainage in Neoplastic Jaundice. Issue 4 (1993) - Audisio, Riccardo A.; Morosi, Carlo; Bozzetti, Federico; Cozzi, Guido; Bellomi, Massimo; Pisani, Paola; Pestalozza, Alessandra; Gennari, Leandro; Severini, Aldo
Abstract : The purpose of this paper is to evaluate factors affecting the outcome of cholangitis after PTBD in jaundiced cancer patients. Twenty nine patients with neoplastic jaundice (male/female ratio 13/16, median age 55 years) with full clinical data, were treated by PTBD and developed cholangitis at a median of 9 days later. Four patients (14%) died of biliary sepsis a median of one month after PTBD while the other 25 survived a median of 6 months, with one week median duration of cholangitis. The probability of the cholangitis resolving was analyzed by time to resolution and it was found that 50% and 100% of the recoveries occurred 5 and 9 months respectively from the onset of the complication. The series was analyzed to determine the role of several variables (disease/patient/treatment related) in the resolution of cholangitis. Only a low stricture site, a large initial drainage catheter (10F) and a temperature increase exceeding 39 ° C were correlated with a positive outcome. We conclude that PTBD-related cholangitis has, in our experience, a good chance of cure, low mortality rate and satisfactory 6 months median survival.